2014
DOI: 10.1152/ajprenal.00134.2014
|View full text |Cite
|
Sign up to set email alerts
|

Role of 2′,3′-cyclic nucleotide 3′-phosphodiesterase in the renal 2′,3′-cAMP-adenosine pathway

Abstract: Energy depletion increases the renal production of 2=,3=-cAMP (a positional isomer of 3=,5=-cAMP that opens mitochondrial permeability transition pores) and 2=,3=-cAMP is converted to 2=-AMP and 3=-AMP, which in turn are metabolized to adenosine. Because the enzymes involved in this "2=,3=-cAMP-adenosine pathway" are unknown, we examined whether 2=,3=-cyclic nucleotide 3=-phosphodiesterase (CNPase) participates in the renal metabolism of 2=,3=-cAMP. Western blotting and real-time PCR demonstrated expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…18 Finally, we observed that, in CNPase +/+ kidneys, energy depletion increases kidney tissue levels of 29,39-cAMP in CNPase 2/2 but not CNPase +/+ kidneys. 18 These findings support the view that kidneys express CNPase and that renal CNPase mediates, in part, the renal metabolism of 29,39-cAMP.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…18 Finally, we observed that, in CNPase +/+ kidneys, energy depletion increases kidney tissue levels of 29,39-cAMP in CNPase 2/2 but not CNPase +/+ kidneys. 18 These findings support the view that kidneys express CNPase and that renal CNPase mediates, in part, the renal metabolism of 29,39-cAMP.…”
Section: Discussionmentioning
confidence: 51%
“…18 Moreover, we found that overexpression of CNPase in kidney cells increases the metabolism of exogenous 29,39-cAMP to 29-AMP and that infusions of 29,39-cAMP into CNPase +/+ kidneys increase renal venous 29-AMP, and this response is diminished in CNPase 2/2 kidneys. 18 Finally, we observed that, in CNPase +/+ kidneys, energy depletion increases kidney tissue levels of 29,39-cAMP in CNPase 2/2 but not CNPase +/+ kidneys. 18 These findings support the view that kidneys express CNPase and that renal CNPase mediates, in part, the renal metabolism of 29,39-cAMP.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations